2022
DOI: 10.3390/children9010108
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Physical Education Teachers’ Perceptions about Their Preparation for Inclusive Education

Abstract: The prevailing rights and quality of life approaches call for the inclusion of people with diversity and/or disabilities in society, including their participation in the educational system. Therefore, different institutions are urging countries to take action to ensure that students with disabilities receive the accommodations and supports they need within the framework of inclusive education. The idiosyncrasies of physical education (PE) classes can be an opportunity to encourage the participation and inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
(47 reference statements)
1
10
0
4
Order By: Relevance
“…These results could be related to the study by Triviño-Amigo et al where the three dimensions mentioned above and, in this case, the years of teaching experience, showed a significant correlation with each other [ 48 ]. However, in the Methodology dimension, the correlation with respect to age range was not significant in the present investigation, in agreement with Rojo-Ramos et al [ 38 , 57 , 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results could be related to the study by Triviño-Amigo et al where the three dimensions mentioned above and, in this case, the years of teaching experience, showed a significant correlation with each other [ 48 ]. However, in the Methodology dimension, the correlation with respect to age range was not significant in the present investigation, in agreement with Rojo-Ramos et al [ 38 , 57 , 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, more research is required to clarify the real attitudes of Saudi PE teachers toward the inclusion of students with different types of disabilities. Another explanation as to why female participants in the current study reported more positive attitudes toward inclusion than their male counterparts could be that the former are willing to attend more courses and have experiences related to inclusive practices ( Rojo-Ramos et al, 2022 ), which may be reflected in their attitudes and feelings toward teaching students with disabilities in their classes.…”
Section: Discussionmentioning
confidence: 88%
“…For example, teachers’ positive attitudes toward students not only encourage learners to be successful in their classes ( Combs et al, 2010 ) and to develop both learning skills and knowledge of the subject matter but are also integral to successful inclusion ( Yada and Savolainen, 2017 ; Saloviita, 2020 ). Consequently, to achieve successful inclusion in PE contexts, it is essential that PE teachers have positive attitudes and are adequately supported ( UNESCO, 2020 ; Rojo-Ramos et al, 2022 ). Such support plays an important role in meeting Sustainable Development Goal 4 ( UNESCO, 2016 ) in ensuring that all students have access to high-quality, inclusive, and equitable education and that opportunities are promoted for lifelong learning.…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, diversos fatores parecem moldar a atitude dos professores face à inclusão, como uma inexistente ou insuficiente formação neste domínio (Wilson, Theriot & Haegele, 2020), seja formação inicial ou contínua, que suporte uma prática refletida, eficiente e personalizada considerando as necessidades, fragilidades e potencialidades únicas do aluno (Rojo-Ramos et al, 2022). Portanto, existe, neste contexto, a necessidade de oferta de formação específica e que perspetive o apoio multidisciplinar.…”
unclassified
“…As barreiras físicas no espaço escolar, as condições de trabalho (espaços acessíveis e material), a aceitação dos alunos com deficiência pelos seus pares não deficientes, as limitações em realizar continuidade pedagógica com o mesmo grupo de alunos e o elevado número de alunos por turma são igualmente reportados como fatores condicionantes da inclusão (Alves, et al, 2017;Yarimkaya, 2021;Rojo-Ramos, et al, 2022;Wang, Qi, & Wang, 2015).…”
unclassified